Rancangan Sistem Informasi Berbasis Web dengan Metode Rapid Application Development (RAD) Pada Perpustakaan Sekolah Menengah Kejuruan - Bachtiar, Yusuf (Journal of Informatics Management and Information Technology, 2025)
The library information system plays a crucial role in supporting academic activities and literacy in educational institutions, including SMK Negeri 1 Babelan. Efficient management of member data, books, borrowing, and returns poses a major challenge when a manual system is still used, as is the case in this school library. This situation slows down the library's workflow and reduces student interest in visiting the library due to the perceived slow performance. The difficulty in locating books on the shelves, the availability of necessary books, and so on often lead to situations where students find that their needs cannot be met when they arrive. The role of information systems in various aspects, including libraries, gives them a competitive advantage. This research develops a desktop library application to facilitate data management from borrowing, returning, book searching, to member administration, aiming to improve operational efficiency and assist staff in daily tasks. The Rapid Application Development (RAD) method was chosen for its quick and iterative development, involving users at every stage. It begins with needs analysis, prototype creation, followed by testing and continuous refinement. This research also aims to simplify the library operating system, which has so far been done manually. The results of Blackbox testing and the outcomes of the program testing show that all functionalities of the buttons and menus on the website are functioning well with an average score of 4.55 from both validators, which falls into the 'very good' category.